Bovine Colostrum to Children With Short Bowel Syndrome: A Randomized, Double-Blind, Crossover Pilot Study. (January 2014) - Aunsholt, Lise; Jeppesen, Palle Bekker; Lund, Pernille; Sangild, Per Torp; Ifaoui, Inge Bøtker Rasmussen; Qvist, Niels; Husby, Steffen
Background : Management of short bowel syndrome (SBS) aims to achieve intestinal autonomy to prevent fluid, electrolyte, and nutrient deficiencies and maintain adequate development. Remnant intestinal adaptation is required to obtain autonomy. In the newborn pig, colostrum has been shown to support intestinal development and hence adaptive processes. Aim : The efficacy of bovine colostrum to improve intestinal function in children with SBS was evaluated by metabolic balance studies. Materials and Methods : Nine children with SBS were included in a randomized, double-blind, crossover study. Twenty percent of enteral fluid intake was replaced with bovine colostrum or a mixed milk diet for 4 weeks, separated by a 4-week washout period. Intestinal absorption of energy and wet weight was used to assess intestinal function and the efficacy of colostrum. Results : Colostrum did not improve energy or wet weight absorption compared with the mixed milk diet ( P = 1.00 and P = .93, respectively). Growth as measured by weight and knemometry did not differ between diets ( P = .93 and P = .28). In these patients, <150% enteral energy absorption of basal metabolic rate and 50% enteral fluid absorption of basal fluid requirement suggested intestinal failure and a need for parenteral nutrition (PN). Conclusion : Inclusion of bovine colostrum to the diet did not improve intestinal function. Metabolic nutrient and wet weight balance studies successfully assessed intestinal function, and this method may distinguish between intestinal insufficiency (non–PN-dependent) and intestinal failure (PN-dependent) patients.